Analysis of the leading sectors of the city of Salatiga in 2009-2012 - ADI SAPUTRO WIJAKSONO (Journal on Economics, Management and Business Technology, 2022)
This thesis aims to determine the leading economic sectors in the City of Salatiga. This study uses secondary data for the period from 2009 to 2012 and the results of research interviews with Salatiga City Government companies: PDAM Salatiga, PT PLN Salatiga Service Unit, PD BPR Bank Salatiga, Office of Transportation Communications, Culture and Tourism Salatiga and PT. Telkom Property/PT. GRAHA SARANA DUTA (GSD) Salatiga. GRDP data for 2009-2012 was processed using the Location Quotient (LQ) approach and the Dynamic Location Quotient (DLQ) approach. The average LQ results for the 2009-2012 period show that there are five (5) basic sectors and 1 basic sub-sector in Salatiga City which are included in the base sector, meaning that these sectors in Salatiga City have a comparative advantage (LQ > 1) namely Livestock Sub Sector (LQ = 1.24), Electricity, Gas and Water Supply Sector (LQ = 6.08), Construction Sector (LQ = 1.07), Transportation and Communication Sector (LQ = 2.90) , the Financial Institutions, Leasing and Corporate Services Sector (LQ = 2.63) and finally the Services Sector (LQ = 1.77). And the average DLQ results for the 2009-2012 period show that there are two (2) sub-sectors that are not yet excellent but have the potential to excel in the future, namely; Food Crops Sub-Sector (DLQ = 1.00) and Fisheries Sub-Sector (DLQ = 1.12) and there is one (1) superior sector and has the potential to excel in the future namely; Construction Sector (DLQ = 1.01). 63) and finally the Services Sector (LQ = 1.77). And the average DLQ results for the 2009-2012 period show that there are two (2) sub-sectors that are not yet excellent but have the potential to excel in the future, namely; Food Crops Sub-Sector (DLQ = 1.00) and Fisheries Sub-Sector (DLQ = 1.12) and there is one (1) superior sector and has the potential to excel in the future namely; Construction Sector (DLQ = 1.01). 63) and finally the Services Sector (LQ = 1.77). And the average DLQ results for the 2009-2012 period show that there are two (2) sub-sectors that are not yet excellent but have the potential to excel in the future, namely; Food Crops Sub-Sector (DLQ = 1.00) and Fisheries Sub-Sector (DLQ = 1.12) and there is one (1) superior sector and has the potential to excel in the future namely; Construction Sector (DLQ = 1.01).